Analysis of the effect of return on assets, debt to equity ratio, net profit margin, earning per share on stock returns in automotive and component sub-sector companies - Simanullang, Sairun; Simanullang, Fransiska (Priviet Social Sciences Journal, 2023)
This research aims to determine the influence of profitability and leverage on stock returns. The sampling technique in this study uses a survey on the Indonesia Stock Exchange. The data analysis methods used include validity and reliability tests, classical assumption tests, regression analysis, correlation and determination coefficient analysis, and hypothesis testing. The results of this research indicate that: Return on Assets has a significant influence on returns in the automotive and component sub-sector companies on the Indonesia Stock Exchange. There is an influence of the debt to equity ratio on stock returns in automotive and component sub-sector companies on the Indonesia Stock Exchange. Net profit margin does not have a significant influence on stock returns. Earning per share influences stock returns in automotive and component sub-sector companies on the Indonesia Stock Exchange. Return on assets, debt to equity ratio, net profit margin, and earning per share influence stock returns in automotive and component companies listed on the Indonesia Stock Exchange during the period 2017-2021.